2016
DOI: 10.1089/bio.2015.0115
|View full text |Cite
|
Sign up to set email alerts
|

Feedback of Individual Genetic Results to Research Participants: Is It Feasible in Europe?

Abstract: Background: There is growing consensus that individual genetic research results that are scientifically robust, analytically valid, and clinically actionable should be offered to research participants. However, the general practice in European research projects is that results are usually not provided to research participants for many reasons. This article reports on the views of European experts and scholars who are members of the European COST Action CHIP ME IS1303 (Citizen's Health through public-private In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“… 14 However, countries have different policies regarding the RoR: some prohibit the return, others provide general guidelines, and many do not have any guidelines. 67 , 99 These conflicting policies are problematic because, within an international consortium, some participants may benefit from the RoR and others not. Additionally, projects could decide not to offer the RoR to avoid conflicts with regulators in countries that restrict or prohibit the RoR.…”
Section: Which Findings Should Be Offered In Psychiatric Genomics Resmentioning
confidence: 99%
“… 14 However, countries have different policies regarding the RoR: some prohibit the return, others provide general guidelines, and many do not have any guidelines. 67 , 99 These conflicting policies are problematic because, within an international consortium, some participants may benefit from the RoR and others not. Additionally, projects could decide not to offer the RoR to avoid conflicts with regulators in countries that restrict or prohibit the RoR.…”
Section: Which Findings Should Be Offered In Psychiatric Genomics Resmentioning
confidence: 99%
“…Limiting return to clinically actionable results was seen as a way to guard against the introduction of harm—which would mean that the opportunity for benefit would accrue to only a small fraction of participants and possibly mostly in the future, as more is learned about effective prevention and treatment targeted to specific traits. These findings point to the importance of setting realistic expectations among participants concerning benefit, careful decisions about which results will be offered, and the commensurate allocation of research resources to support an ethical process of return, potentially including individualized interpretation, counseling, and referral [ 24 28 ]. It is essential to balance the use of limited research resources for these purposes with two key obligations: maintaining fidelity to the goal of generating generalizable knowledge for the benefit of all, and avoiding the perpetuation of misconceptions about the nature research.…”
Section: Discussionmentioning
confidence: 99%
“…It has been increasingly demonstrated that biobanks should inform genomic results to donors [11] but there are only a few concrete examples, partly due to many legal, financial, organizational, and societal challenges that need to be tackled first [12]. Some biobanks have tested a model for contacting donors to inform them about certain results, as described by Haukkala et al [13] and Leitsalu et al [14].…”
Section: Discussionmentioning
confidence: 99%
“…Lack of qualified staff is also a problem, since clinical geneticists and/or genetic counselors are few and primarily needed in clinical practice. Thus, practical challenges outweigh the legal ones [12]. When biobanks start to concretely plan the processes of returning results, different attempts to solve the practical obstacles will need to be carefully investigated.…”
Section: Discussionmentioning
confidence: 99%